Proximity-Based Maritime Internet of Things: A Service-Centric Design - Michael M. Wang; Jingjing Zhang; Xiaohu You (IEEE Access, 2023)
The Internet of Things (IoT) is all about services. The proximity-based IoT service is a type of service that becomes available once an IoT object comes near other objects. This type of service typically involves proximity machine-type communication (MTC) that allows direct communication between objects in a spatiotemporal context on an ad-hoc basis. The IoT world has witnessed increasing cases of such applications in recent years, but proximity MTC has not received sufficient attention in the IoT community. As such, this paper presents the unique characteristics and requirements of proximity MTC, focusing on differentiating proximity MTC from infrastructure-based wide-area MTC and service-centric networking from host-centric networking. Specifically, the paper utilizes an emerging application in maritime IoT, maritime autonomous surface shipping (MASS), as an example and offers an insightful and rigorous examination of the legacy maritime communications technology, pointing out the pitfalls to avoid in the development and standardization of proximity MTC in light of the recent spectrum assignment by ITU. A comprehensive service-centric solution is presented to address the requirements and pitfalls, highlighting its significance and relevance to virtual sensing in applications like MASS. The paper thoroughly describes the network architecture and how different network components and layer protocols fit together to deliver desired functionalities to meet the service-centric requirements through a concrete design.